2019
DOI: 10.1186/s13046-019-1032-3
|View full text |Cite
|
Sign up to set email alerts
|

PAGE4 promotes prostate cancer cells survive under oxidative stress through modulating MAPK/JNK/ERK pathway

Abstract: BackgroundProstate cancer (PCa) is one of the most common cancers in male worldwide. Oxidative stress has been recognized as one of the driving signals pathologically linked to PCa progression. Nevertheless, the association of oxidative stress with PCa progression remains unclear.MethodsWestern blot, q-RT-PCR and bioinformatics analyses were used to examine PAGE4 expression. Comet assay and Annexin V/ PI dual staining assay were performed to investigate DNA damage and cell death under oxidative stress. Mouse x… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 51 publications
(60 reference statements)
0
19
0
Order By: Relevance
“…The MAPK/ERK signaling pathway is mainly related to cell proliferation and differentiation, while the MAPK/JNK and MAPK/p38 pathways are closely related to apoptosis of cells 23 . Activation of MAPK/ERK signaling pathway promotes the growth of prostate cancer 24 , cervical cancer 25 , thyroid cancer 26 , and breast cancer 27 . MAPK/ERK-induced epithelial-mesenchymal transition promotes migration and metastasis of lung cancer cells 28 .…”
Section: Introductionmentioning
confidence: 99%
“…The MAPK/ERK signaling pathway is mainly related to cell proliferation and differentiation, while the MAPK/JNK and MAPK/p38 pathways are closely related to apoptosis of cells 23 . Activation of MAPK/ERK signaling pathway promotes the growth of prostate cancer 24 , cervical cancer 25 , thyroid cancer 26 , and breast cancer 27 . MAPK/ERK-induced epithelial-mesenchymal transition promotes migration and metastasis of lung cancer cells 28 .…”
Section: Introductionmentioning
confidence: 99%
“…6 Furthermore, treatment with H 2 O 2 significantly increased the expression of PAGE4 in PCa cells, which protected cells from apoptosis, potentially through modulating mitogen-activated protein kinase pathway. 12 Finally, multiple studies have reported that, at least at the RNA level, PAGE4 is undetectable in metastatic PCa. 7,10,11,13 The significance of PAGE4 in PCa development and progression is highlighted by the fact that (a) expression of PAGE4messenger RNA (mRNA) is inversely correlated with Gleason score, 11 (b) decreased expression of PAGE4-mRNA in patients with PCa predicts an increased risk of biological recurrence, 10 and (c) PAGE4 levels correlate positively with, and predict survival of, patients with hormone-naive PCa.…”
Section: Introductionmentioning
confidence: 99%
“…A study has reported that, under the oxidative stress condition, the prostate-associated gene 4 (PAGE4) expression also increases, which subsequently avoids cancer cell apoptosis. 18 PAGE4 is a highly intrinsically disordered protein, whereas protein overexpression could protect the cells from stress-induced death. 19 Another study has reported that cancer cells can ignore the signals that are important for preventing cell division or the beginning of a process known as "programmed cell death," whereby the body tends to dispose of its abnormal cells by increasing CD47 production.…”
Section: Discussionmentioning
confidence: 99%